2005
DOI: 10.1007/s10038-005-0341-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci in ABCA1 modify cerebrospinal fluid amyloid-β1-42 and plasma apolipoprotein levels

Abstract: The ATP-binding cassette transporter A1 encoded by ABCA1 plays an integral role in the efflux of cellular cholesterol and phospholipids, but may also be a central mediator of b-amyloid (Ab) processing. Here, genetic association of the common R219K variant of ABCA1 is shown with cerebrospinal fluid (CSF) Ab 1-42 levels, reinforcing emerging evidence of a connection between lipid and Ab metabolism. In support of this finding we demonstrate for the first time that CSF cholesterol and Ab 1-42 are correlated. To af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 57 publications
3
9
0
Order By: Relevance
“…A weakness of our study is the lack of measures of lipids in CSF or Aβ in serum/plasma. We have however previously reported that CSF Aβ and total cholesterol are correlated [25], though sample sizes were in our view too small to test for APOE association with CSF cholesterol. Monitoring multiple lipid traits in addition to other Aβ fragments in both serum and CSF would help to further resolve these issues.…”
Section: Discussionmentioning
confidence: 76%
“…A weakness of our study is the lack of measures of lipids in CSF or Aβ in serum/plasma. We have however previously reported that CSF Aβ and total cholesterol are correlated [25], though sample sizes were in our view too small to test for APOE association with CSF cholesterol. Monitoring multiple lipid traits in addition to other Aβ fragments in both serum and CSF would help to further resolve these issues.…”
Section: Discussionmentioning
confidence: 76%
“…Apoprotein B was the exclusive apolipoprotein of LDL‐C that is normally found only in the periphery. It has been reported that total cholesterol level has strong correlations with LDL‐C and ApoB levels . Previous research have shown that rabbits fed a cholesterol‐enriched diet exhibited increased level of Aβ in brain as well as lysosomal dysfunction in neurons .…”
Section: Discussionmentioning
confidence: 99%
“…KK genotype of ABCA1R219K polymorphisms has been reported linked to a 5.5% higher concentration of small HDL particles [93]. Moreover, controversial conclusion may vary with other factors such as age [94], gender [95], smoking [96], obesity [97]and existing linkage disequilibrium or interactive effect with other candidate genes [98]. In addition, the influence of ABCA1 gene variants on other lipid molecules and enzymes secondarily can mildly influence HDL concentration.…”
Section: Discussionmentioning
confidence: 99%